The problems of genocide : permanent security and the language of transgression - Moses, A. Dirk 1967- (Human rights in history, 2021)
"Genocide is a problem: not only the terrible fact of mass death, but also how the relatively new idea and law of genocide organises and distorts our thinking about civilian destruction. Taking the normative perspective of civilian immunity from military attack, this book argues that the implicit hierarchy of international law, atop which sits genocide as the "crime of crimes," blinds us to other types of humanly caused civilian death, like bombing cities, the "collateral damage" of missile and drone strikes, blockades, and sanctions. In other words, talk of genocide functions ideologically to detract from systematic violence against civilians perpetrated by governments. The Problems of Genocide also contends that this violence is the consequence of "permanent security" imperatives: the striving of states, and armed groups seeking to found states, to make themselves invulnerable to threats. To solve the problems of genocide, this book proposes replacing it with permanent security, which should be criminalized"--